The effect of probiotics on surgical outcomes in patients with gastric cancer: a meta-analysis of randomized controlled trials - Ye, Wei; Dong, Bo; Li, Guanglin; Zhang, Yuqiang (Frontiers in Surgery, 2023)
The effect of probiotics on postoperative infectious complications and nutritional status in patients with gastric cancer is still controversial, and a comprehensive search and analysis of the current relevant evidence is necessary. Our study aimed to define the effects of probiotics on surgical outcomes in gastric cancer patients undergoing surgery. Up to June 20, 2023, Embase, PubMed, Web of Science, and Cochrane databases were searched for randomized controlled trials of probiotics in gastric cancer patients undergoing surgery. Relative risk (RR) or mean difference (MD) was used to calculate the effect sizes using RevMan 5.3. A total of nine studies reporting on 861 participants were included. Perioperative supplementation with probiotics did not improve weight loss (MD 0.73 kg; 95% CI: -0.56, 2.02) or serum prealbumin levels (MD 9.48 mg/L; 95% CI: -3.43, 22.40), but did reduce the incidence of postoperative infectious complications (RR 0.46, 95% CI 0.28, 0.77), shorten the time to first exhaust , the time to first defecation (MD -15.71 hours; 95% CI: -25.62, -5.79), and the length of hospital stay (MD -0.94 days; 95% CI: -1.33, -0.55), and increase serum albumin levels (MD 0.73 g/L; 95% CI: 0.01, 1.46) in gastric cancer patients undergoing surgery. Probiotics are effective in preventing postoperative infectious complications, promoting postoperative recovery, and improving nutritional status in gastric cancer patients undergoing surgery. Our study highlights the importance of probiotics for healthcare systems and offers a potential strategy to improve the prognosis and reduce the medical burden of gastric cancer patients undergoing surgery.